Country Gender Assessment : Georgia - World Bank (World Bank, Washington, DC, 2021)
This Country Gender Assessment (CGA) provides empirical evidence and analyses equality between the women and men of Georgia. Methodologically, the report adopts the Gender Assessment framework proposed by the World Development Report on Gender Equality and Development (WDR 2012) to analyze recent progress and pending challenges in gender equity, across three key dimensions: (a) endowments, (b) economic opportunities, and (c) agency and Voice. Based on this framework, extensive research was conducted to identify available data sources and empirical evidence, on indicators such as poverty, health, education, perceptions, and wellbeing, among others affecting gender equity in Georgia. In addition to its intrinsic value, promoting gender equality is a central priority to reduce poverty, boost shared prosperity, and advance the aspirations of the middle class. Georgia’s development challenges entail adjusting and refining the country’s growth paradigm, and translating economic growth to more rapid, sustainable poverty reductions (World Bank 2018a). However, sustained growth, poverty reduction, and shared prosperity require that economic gains improve welfare among all communities, households, and individuals (World Bank 2019). Promoting women’s economic opportunities, access to endowments, and voice and agency is fundamental in tackling some of Georgia’s main policy challenges, including raising labor productivity, integrating with the global economy, and invigorating stagnant rural areas (World Bank 2018a). Moreover, the socioeconomic impacts derived from the COVID-19 pandemic present countries with an inflexion point, to either enhance gender equality and benefit from its long-term benefits, or to risk losing fundamental progress in gender issues, and forego development opportunities in the future.